Special Section: Competitive Strategy, Economics, and Information Systems - Clemons, E.K. (Institutional Knowledge at Singapore Management University, 2010)
This special section on competitive strategy, economics, and information systems (IS) focuses on important current themes in this area of the discipline. The papers, whose initial versions were presented in and selected from the Competitive Strategy, Economics, and Information Systems Mini-Track of the 2010 Hawaii International Conference on System Sciences, address a broad range of topics, including bundle pricing, price dispersion, business process outsourcing, and the intersection of economics, strategy, and antitrust law.